(untitled) (Scientific journal of the Fergana State University, 2023)
This article discusses the semantic and stylistic factors that provide imagery through non-own quotations. It is known that speech is a very complex process, so the speaker cannot always express his attitude to the listener as he wants. In such situations, the words that have been actively used by the speaker in everyday speech, in his opinion, become incapable of expressing his emotional-expressive attitude to the things and objects or persons to which the speech is directed. Imagery is based on metaphors, which serve to express attitude and emotional expressiveness is the most convenient means of expression. Figurativeness, as a phenomenon characteristic of any metaphorical application, plays an important role in various forms of speech, in particular, in artistic texts, in the form of a quote that is not one’s own. At this point, in artistic texts, the use of quotations that are not one’s own is intended to illuminate the character’s characteristics, his inner experiences, and his attitude to the surrounding people, so the words expressing attitude have an important place in them. it is natural to occupy.